Jupiter's equatorial X-ray emissions over two solar cycles. Issue 4 (25th March 2023) - Wibisono, A D; Branduardi-Raymont, G; Coates, A J; Dunn, W R; French, R J
ABSTRACT: Jupiter's disc is bright in X-rays as H2 molecules in the atmosphere are very effective at scattering solar X-rays. K-shell fluorescence from carbon atoms in atmospheric methane is thought to also provide a minor contribution. XMM–Newton has now observed Jupiter over a span of nearly two solar cycles from 2003 to 2021, offering the opportunity to determine whether Jupiter's disc emissions are driven by solar activity or not. We compare the count rates of X-rays of energies 0.2–10.0, 0.2–2.0, 2.1–5.0, and 5.1–10.0 keV from the planet's equatorial region, with the sunspot number and F10.7 adjusted solar radio flux. The respective Pearson's correlation coefficients for both are 0.88/0.84, 0.86/0.83, 0.40/0.34, and 0.29/0.22 for each energy demonstrating that the low-energy X-ray disc emissions are indeed controlled by the Sun's activity. This relationship is less clear for the higher energy emissions, raising questions around the source of these emissions.